The strength properties of oriented strand board from pine species including thickness swelling, water absorption and internal bond / Yusri Yusmaidi - Yusmaidi, Yusri (2002)
The Water Absorption, Thickness Swelling and Internal Bond bonding properties of OSB from pine species were studied. Higher Water Absorption ratio was defected from sample with high density. Similar trend of greater values from sample with high density was observed for Thickness Swelling. While for Internal Bonding it was cleared that sample with higher density carries better readings for Internal Bond. Thus, density plays an important role to lesser the matter Absorption ratio and furthermore perverting Thickness Swelling while support the Internal Bonding. With this, the data fainted is hoped to be used as guidance to view the ability and suitably for the use of OSB made from Pine species as a medium in parts and places which are exposed to moisture.